2014
DOI: 10.1159/000354830
|View full text |Cite
|
Sign up to set email alerts
|

Myeloma in Scar Tissue - An Underreported Phenomenon or an Emerging Entity in the Novel Agents' Era? A Single Center Series

Abstract: Tumor relapse in scar tissue is uncommon in cancer patients. Likewise, extramedullary plasmacytoma (EMP) relapse in scar tissue in the setting of multiple myeloma (MM) has been rarely reported. We report a series of 3 patients whose disease progressed as EMP at the site of a wound from previous invasive procedures. All 3 patients were treated for the relapsed disease with different treatment modalities, but failed to respond adequately and died several months after relapse. At original MM diagnosis, all had ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Furthermore, cases of extramedullary plasmocytoma localized at the site of wound healing from previous invasive bone procedures have been reported [35]; however, the pathophysiological mechanisms are not clearly understood [36]. The present case report constitutes a different entity since the MM proliferation occurred in bone.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, cases of extramedullary plasmocytoma localized at the site of wound healing from previous invasive bone procedures have been reported [35]; however, the pathophysiological mechanisms are not clearly understood [36]. The present case report constitutes a different entity since the MM proliferation occurred in bone.…”
Section: Discussionmentioning
confidence: 81%
“…Consistent with this hypothesis, it has been shown that in the severe combined immunodeficiency human myeloma model, cells from patients with EMPs injected directly to the fetal bone graft are capable of proliferating and grow in contiguous soft tissues beyond the bone graft, consistent with the clinical behavior of myeloma cells in some patients [8]. Clinicians should be aware of the possibility of this type of relapse in order to plan the best treatment approach, although with the current available therapies, including the so-called lymphoma-like regimens, the prognosis remains poor [1,6,7,8]. …”
mentioning
confidence: 97%
“…In this issue of Acta Haematologica , Muchtar et al [6 ]report a series of 3 patients with relapsed MM whose disease progressed with EMPs at the scars of previous surgical procedures. All 3 had initially been treated with novel agents and 2 of them with autologous stem-cell transplantation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some possible mechanisms are: (i) decreased expression of adhesion molecules, such as CD44, or loss of CD56, which could result in disease dissemination by impairing the adhesion of malignant plasma cells to the bone marrow endothelium, (ii) low expression of chemokine receptors or downregulation of CXCR4 and its ligand CXCL12 (previously termed SDF‐1α), which is linked to the bone marrow homing of myeloma cells, (iii) increased angiogenesis or (iv) bone marrow hypoxia resulting in egression of bone marrow plasma cells (Vande Broek et al , ; Bladé et al , ). Concerning EMD arising from scars after surgical procedures, it has been hypothesized that the inflammatory process derived from tissue surgery could facilitate the migration of myeloma cells and constitute a reservoir of dormant myeloma cells able to proliferate leading to a localized relapse (Fernández de Larrea et al , ; Muchtar et al , ; Rosiñol et al , ). Finally, extramedullary involvement was recently reported to be significantly higher in patients with high‐risk myeloma defined by gene expression profiling (Usmani et al , ).…”
mentioning
confidence: 99%